Molecular dynamics simulation of CO2 separation from integrated gasification combined cycle syngas via the hydrate formation - Yan Ke-Feng; Li Xiao-Sen; Chen Zhao-Yang; Xu Chun-Gang (2010)
Molecular dynamics (MD) simulation is used to study the microscopic mechanism of CO2 separation from integrated gasification combined cycle (IGCC) syngas (CO2/H-2) via the hydrate formation The stable structures and microscopic properties of CO2 hydrate, H-2 hydrate, and CO2/H-2 hydrate from one stage separation for IGCC syngas are investigated systematically. The binding energy for loading the hydrate structure with the guest molecules, Delta E-n was analyzed It was shown that the binding between CO2 and water is more stable than that between H-2 and water That is, CO2 can more easily form the hydrate Therefore. CO2 in the CO2/H-2 gas mixture more easily transfers into the hydrate phase. Based on this, CO2 can be separated from the IGCC syngas. The binding energy for loading the single cavity with the guest molecules, Delta E-GH, was analyzed It was found that the gas mixture can form structure I (SI) hydrate, in which CO2 molecules preferably occupy the big cavity and then occupy the small cavity, and H-2 molecules only occupy the small cavity. The simulation was carried out at pressure of 8.5 MPa and temperature of 273.7 K for the stable structure of the CO2/H-2, hydrate in one stage separation for IGCC syngas From the Delta E-n and Delta E-GH of the systems with H-2 single and double occupancy in the small cavity, it is concluded that the configurations with the single occupancy is most stable. The stable structure of the hydrate in one stage separation is attained by MD. It provides a theoretical evidence Of CO2 separation for formation hydrate in IGCC syngas.